EFEKTIFITAS CAMPURAN DAUN KAYU PUTIH (Melaleuca eucadendra) DAN LIMBAH KERTAS HVS SEBAGAI BIOATRAKTAN PADA RAYAP TANAH (Coptotermes sp) - Septiana, Tessa; Husni, Harnani (Universitas Tanjungpura, 2017)
At recent year, termite control strategies is still using of synthetic termiticide which is applied either by soil treatment, wood preservation or impregnation of the thermiside into the target. This control technique is very effective and beable to protect buildings and agricultural crops from termite attack, on the other hand, synthetic termite can pollute the environment and potentially poison to human. Therefore, it is necessary to develop termite control technology using baiting system, which is made from natural material as environmentally friendly. Eucalyptus leaves are potentially used as attractants for termite control by bait method. The test was conducted in two methods: no-choice test and two-choice test, using 5 treatment composition, eucalyptus leaves: official waste paper, 80%: 20%, 60%: 40, 40% : 60%, 80% : 20%, and 0% : 100% as control. The results showed that the mixing of eucalyptus leaf (Melaleuca leucadendra) and official waste paper at composition of 60%: 40% was effective as bioatractant to termites (Coptotermes sp). Keywords: bio-attractants, eucalyptus leaves, official waste paper, subterranean (Coptotermes sp).